Osteoporosis and the Marfan syndrome. Issue 811 (May 1993) - Gray, J. R.; Bridges, A. B.; Mole, P. A.; Pringle, T.; Boxer, M.; Paterson, C. R.
Abstract : Fourteen patients with Marfan syndrome, defined according to present criteria, had bone mineral content of the distal forearm measured by single photon absorptiometry. Patients were matched for age and sex with a large local group of healthy volunteers. While further work is needed with other methods of densitometry with measurements at other sites, our results provide no evidence that there is an increased incidence of osteoporosis in Marfan syndrome. Previous reports of an association were probably due to incorrect clinical diagnosis or confusion with clinically similar syndromes known to cause osteoporosis.